1958
DOI: 10.1021/ie50578a025
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiolysis. Tributyl Phosphate and Its Diluent Systems

Abstract: Tributyl Phosphate and Its Diluent Systems One factor which makes tributyl phosphate one of the most important solvents for processing nuclear fuels is its chemical stability. However, degradation reactions give butyl acid phosphates which may react with metal ions being separated (2) and must, therefore, be kept at low concentrations. Because radiation damage may lead to similar products, radiolysis, not only of pure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1962
1962
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 1 publication
3
19
0
Order By: Relevance
“…[67] Many early studies of the radiation chemistry of TBP involved irradiation of the neat compound. [82,86,88] However, it was quickly realized that diluents and aqueous phases altered radiolysis product yields. [81,88] Unfortunately, few studies have been done under conditions that allow direct comparison.…”
Section: Degradation Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…[67] Many early studies of the radiation chemistry of TBP involved irradiation of the neat compound. [82,86,88] However, it was quickly realized that diluents and aqueous phases altered radiolysis product yields. [81,88] Unfortunately, few studies have been done under conditions that allow direct comparison.…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…[82,86,88] However, it was quickly realized that diluents and aqueous phases altered radiolysis product yields. [81,88] Unfortunately, few studies have been done under conditions that allow direct comparison. During solvent extraction, TBP is irradiated as a complex with water, acid, and/or metals, and these complexes react at different rates with the produced radiolytic reactive species, altering competition kinetics and thus product yields.…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…Therefore, the uranyl complex and NaDBP concentrations should not exceed O.01 M and O.02 M, respectively, in the Na2C03 solution, which requires a carbonate scrub volume of 2500 liters/MTHM. Third, the concentration of Na2MBP is approximately one-third that of NaDBP, assuming no losses of H 2 MBP during HN0 3 scrubbing (17). In addition to the above constituents, the Na2C03 scrub waste will also contain a certain amount of NaHC03 and NaN03 from the neutralization of HNO3 present in the TBP.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Kulikov et al [24] and Nowak et al [25] have reported an increase in the yield of HDBP in the presence of uranium. However, Williams and Wilkinson [15], Becker et al [20] and Burger and McClanahan [37] held the view of a protective effect of uranium on the 30 % TBP/CCl 4 system against radiolysis. Unfortunately, our present experimental results only indicate that there is a competitive relationship between UO 2 2?…”
Section: Plutonium Retention Testmentioning
confidence: 99%